2019
DOI: 10.18410/jebmh/2019/293
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Asymptomatic Bacteriuria in Patients With Diabetes Mellitus in a Year-Long Follow Up Study

Abstract: BACKGROUNDDiabetes mellitus is a major public health problem worldwide today. It affects the genitourinary system. It predisposes patients to a variety of urinary tract infections and has long term effects on patient health. Asymptomatic bacteriuria (ASB) in diabetic patients, its effects on renal function, microalbuminuria, hypertension are not clearly defined. This study was carried out to determine the prevalence of asymptomatic bacteriuria, its clinical and microbiological outcomes in Indian diabetic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Diabetes mellitus has a range of effects on various organ systems [3] a 1940 autopsy study showed that 18% of the subjects with diabetes had a urinary tract infection (UTI) [2] . Also diabetic patients are prone to asymptomatic UTI [4] . The spectrum of UTI in these patients ranges from asymptomatic bacteriuria (ASB) to lower UTI (cystitis), pyelonephritis, and severe urosepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus has a range of effects on various organ systems [3] a 1940 autopsy study showed that 18% of the subjects with diabetes had a urinary tract infection (UTI) [2] . Also diabetic patients are prone to asymptomatic UTI [4] . The spectrum of UTI in these patients ranges from asymptomatic bacteriuria (ASB) to lower UTI (cystitis), pyelonephritis, and severe urosepsis.…”
Section: Introductionmentioning
confidence: 99%